Penerapan Teknologi Watermark Sebagai Upaya Perlindungan Hak Cipta Film pada Platform Bioskoponline.com - Mahendra, Irwansyah Dhiaulhaq; Njatrijani, Rinitami (Faculty of Law, Diponegoro University, 2023)
Digitalization provides option for film-maker industry to penetrate their film release into digital mediums through film streaming platforms, one of which is Bioskop Online. Along with the ease of accessing film digitally, there is still a criminal loophole such as piracy or hijacking that goes alongside. The purpose of this reseacrh is to analyze copyrights protection on films that are released on film streaming platforms according to Law Number 28 of 2014 concerning Copyright, and also the implementation of watermark technology applied by Bioskop Online as an effort to protect the copyright of content in it. This research using normative juridicial research method through a statute approach, also using secondary data sources and another supporting data in the form of interviews with Head of Content in Bioskop Online platform. The results concluded that films that released in Bioskop Online streaming platform is legally protected by the Copyright Law. Furthermore, the watermark technology used by Bioskop Online is also protected by Copyright Law as a copyright management information, copyright electronic information, and a technological protection measures.